1998
DOI: 10.1038/sj.onc.1201551
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic acid activates Jun N-terminal kinase in vascular smooth muscle cells

Abstract: We have previously demonstrated that arachidonic acid activates extracellular signal-regulated protein kinases (ERKs) group of mitogen-activated protein kinases (MAPKs) in vascular smooth muscle cells (VSMC). To understand the role of arachidonic acid in cellular signaling events, we have now studied its eect on jun N-terminal kinases (JNKs) group of MAPKs in VSMC. Arachidonic acid activated JNK1 in a time-and concentration-dependent manner with maximum eects at 10 min and 50 mM. Induced activation of JNK1 by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 38 publications
(64 reference statements)
4
29
0
Order By: Relevance
“…As noted above, TNF-␣ activates JNK in some cell types, 38 and JNK has been shown to be redox sensitive. 42 However, to date, no role for JNK in MCP-1 mRNA upregulation has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted above, TNF-␣ activates JNK in some cell types, 38 and JNK has been shown to be redox sensitive. 42 However, to date, no role for JNK in MCP-1 mRNA upregulation has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…In VSMCs, TNF-␣ stimulates ERK1/2 and p38MAPK ( Figure 4 and References 13, 36, and 37), as well as JNK. 38 Furthermore, we have previously shown that p38MAPK but not ERK1/2 is downstream from agonist-induced ROS production in these cells. 17,31 The role of MAPK in TNF-␣-mediated MCP-1 induction, however, has not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…Epoxygenase metabolites are not known to be involved in cell adhesion although there are reports suggesting that they act in other signaling pathways (Madamanchi et al, 1998;Chen et al, 1999). Conversely, the LOX and COX pathways are widely involved in signaling a variety of cellular functions.…”
Section: Introductionmentioning
confidence: 99%
“…The 85-kDa cytosolic PLA2 (cPLA2) is a major source of intracellular AA release in signal transduction, because it exhibits specificity for phospholipids with AA in the sn2 position, whereas calcium-independent PLA2 (iPLA2) and the secretory PLA2 (sPLA2) do not show the same preference (reviewed in Murakami et al, 1997;Balsinde et al, 1999). AA participates in multiple signaling pathways by providing substrate to three types of oxidative enzymes, LOXs, COXs, and epoxygenase (EOX), all of which participate in diverse signal transduction pathways (reviewed in Piomelli, 1993;Seeds and Bass, 1999).Epoxygenase metabolites are not known to be involved in cell adhesion although there are reports suggesting that they act in other signaling pathways (Madamanchi et al, 1998;Chen et al, 1999). Conversely, the LOX and COX pathways are widely involved in signaling a variety of cellular functions.…”
mentioning
confidence: 99%
“…NDGA similarly activated JNK1/2 and p38 mapk but had no effect on ERK1/2 activation in SW 850 and C4-I cells. Again, this effect of NDGA is likely to be cell type specific: No effect of NDGA on JNK activation could be demonstrated in vascular smooth muscle cells (Madamanchi et al, 1998), HeLa cells and HL 60 cells (Hii et al, 1998). There is some controversy regarding the possible role of stress activated protein kinases as mediators of apoptosis.…”
Section: Experimental Therapeuticsmentioning
confidence: 99%